What should the GP know about nuclear medicine? - Sowiński, Jerzy (Przewodnik Lekarza/Guide for GPs, 2011)
Dynamic development of nuclear medicine brings out systematically increasing participation of radioisotope techniques in both diagnostics and therapy of wide spectrum of diseases. It requires constant training of nuclear medicine specialists but also primary care physicians. The paper presents the basic knowledge on the physical properties and methods of production of radioactive chemical elements. Additionally, techniques of measurement and monitoring of radioactivity of radiopharmaceuticals most frequently used in diagnostics and treatment are described. The paper ends with the discussion on the fundamental problems of radiation protection.